IMPROVING STUDENTS’ SPEAKING SKILLS WITH GREETING MATERIALS USING ICE BREAKING TECHNIQUE AT THE 7th CLASS B SMP QUBA SORONG CITY - Mahu, Fijrinia; Hasbullah; Suharmoko (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2024)
Improving sstudents’ speaking skills with greeting materials using ice breaking technique at the 7th Class B SMP Quba Sorong City. enhance English-speaking skills among 7th-grade students at SMP Quba, Sorong City. The research was conducted on May 20, 2024, following a pre-research phase during a field practice program from August to October 2023. The teacher modified the materials focusing on greetings, and implemented a technique termed “ice breaking.” This technique was performed at the beginning of each English lesson, where students would repeatedly practice greeting phrases until they mastered them, sometimes requiring multiple sessions. The study utilized a descriptive qualitative research technique, incorporating observations and documentation to assess the effectiveness of the ice-breaking method. Despite the challenge of limited observation sessions, the findings revealed that while most students eventually performed the technique without relying on text, some still required additional practice. The research presented the findings which detailed the collected data, and the discussion, which interprets the context of improving students’ speaking abilities through the ice-breaking technique